DIVISION III: COMMISSION 22: METEORS, METEORITES AND INTERPLANETARY DUST. (13th August 2015) - Jenniskens, Peter; Borovička, Jiří; Watanabe, Junichi; Consolmagno, Guy; Jopek(Secretary), Tadeusz; Vaubaillon, Jeremie; Abe, Shinsuke; Janches, Diego; Ryabova, Galina; Ishiguro, Masateru; Zhu, Jin
Abstract : The business meeting of commission 22 was held at the room 403 on 24 th August 2012 (14:00-15:30) in the China National Convention Center in Beijing.